2019
DOI: 10.1038/s41559-019-1015-y
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of protocell self-assembly from mixed amphiphiles at the origin of life

Abstract: Vesicles formed from single-chain amphiphiles (SCAs) such as fatty acids likely played an important role in the origin of life. A major criticism of the hypothesis that life arose in an early ocean hydrothermal environment is that hot temperatures, large pH gradients, high salinity and abundant divalent cations should preclude vesicle formation. But these arguments are based on model vesicles using 1-3 SCAs, even though Fischer-Tropsch-type synthesis under hydrothermal conditions produces a wide array of fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 72 publications
6
120
0
Order By: Relevance
“…In our current study we show that a temperature increase significantly accelerates the formation of membrane compartments and further initiates their fusion, which supports the recent findings of Jordan et al 7 . The accelerated nucleation and growth lead to maturation of compartments, which eventually establish physical contact.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In our current study we show that a temperature increase significantly accelerates the formation of membrane compartments and further initiates their fusion, which supports the recent findings of Jordan et al 7 . The accelerated nucleation and growth lead to maturation of compartments, which eventually establish physical contact.…”
supporting
confidence: 93%
“…This temperature range also represents the conditions in warm ponds: 50-80 °C 42 . Recent evidence shows that the mixtures of single chain amphiphiles form vesicles most readily at temperatures of ~70 °C in aqueous solutions containing mono-and divalent cations in broad pH range 7 . In the light of these observations, it appears that warm temperatures of ponds or LCHFs can allow and even favor protocell compartmentalization.…”
Section: Impact Of Temperature In the Context Of Origin Of Lifementioning
confidence: 99%
“…Mineral cavities within vent rock formations have also been proposed to serve as compartments for primitive forms of life (Lane and Martin, 2012;Russell et al, 2014;Weiss et al, 2016). A recent report demonstrated that certain selected lipid mixtures could assemble into vesicles at 70C in the alkaline water of ''white smoker'' vents ( Jordan et al, 2019). Monnard and Deamer (2002) also showed that specialized lipid mixtures could form stable membranes in seawater at ordinary temperatures and pH ranges.…”
Section: Figmentioning
confidence: 99%
“…The hydrothermal vent hypothesis which has been criticized for allowing excessively high temperatures, salinity and pH gradients is, after the discovery of "Lost City"-type hydrothermal fields (LCHFs), being reconsidered 42 . LCHFs accommodate temperatures between 40 and 90 °C, which could have promoted the formation of prebiotic membrane compartments 43 . In our study, temperature increase weakens membrane-surface adhesion and causes immediate surface de-wetting 17 , facilitating the subcompartment formation.…”
Section: Temperature-enhanced Formationmentioning
confidence: 99%